2022
DOI: 10.1119/5.0086802
|View full text |Cite
|
Sign up to set email alerts
|

Efimov effect for two particles on a semi-infinite line

Abstract: The Efimov effect (in a broad sense) refers to the onset of a geometric sequence of many-body bound states as a consequence of the breakdown of continuous scale invariance to discrete scale invariance. While originally discovered in three-body problems in three dimensions, the Efimov effect has now been known to appear in a wide spectrum of many-body problems in various dimensions. Here, we introduce a simple, exactly solvable toy model of two identical bosons in one dimension that exhibits the Efimov effect. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…We showed that, in addition to the unbroken phase, there exist two additional phases in the scale-invariant two-body problem: one is the discrete scale invariant phase in which two distinct geometric series of two-body bound states appear, and the other is the discrete scale invariant phase in which a single geometric series of two-body bound states appear. This is in sharp contrast to the two-body problem of identical particles on the half line [6], where there arises at most a single geometric series of two-body bound states.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We showed that, in addition to the unbroken phase, there exist two additional phases in the scale-invariant two-body problem: one is the discrete scale invariant phase in which two distinct geometric series of two-body bound states appear, and the other is the discrete scale invariant phase in which a single geometric series of two-body bound states appear. This is in sharp contrast to the two-body problem of identical particles on the half line [6], where there arises at most a single geometric series of two-body bound states.…”
Section: Discussionmentioning
confidence: 76%
“…This paper is aimed at studying breakdown of continuous scale invariance to discrete scale invariance under the (2) family of two-body contact interactions. To simplify the analysis, we shall focus on two-body problems on the half line, which is exactly solvable and known to exhibit discrete scale invariance for the case of identical particles [6]. We shall show that, in a certain subspace of the parameter space of (2), there arise two distinct channels that admit geometric sequences of two-body bound states.…”
Section: Introductionmentioning
confidence: 99%